Punkty widzenia niepełnosprawności – problemy rodziny z niepełnosprawnym bliskim - Hinc, Danuta (Karkonoska Państwowa Szkoła Wyższa, 2011)
Subject of my work encompasses all issues relating to family life with a disabled person. In this article I went into the situation of both parents of a disable child, their relationship between themselves and offspring, both healthy and sick, and also described the living conditions of handicapped siblings. The text also includes a description of the family in which children are healthy while parents are facing deficits. In my work I focused mainly on problems that relatives of a handicapped person need to face – the first shock when they find out about the sickness, an internal struggle with their own opinions, the reorganization of life and breaking the shame and fear. The purpose of my article is to show the reader realities of living under one roof with a disable person, to confront him with a situation which can affect anyone of us, forcing to ask the question: Am I really tolerant?
Keywords: tolerancja; akceptacja; niepełnosprawność; upośledzenie; deficyty; choroba; rodzina; dziecko